Baseline-free damage identification of metallic sandwich panels with truss core based on vibration characteristics. (January 2017) - Lu, Lingling; Song, Hongwei; Yuan, Wu; Huang, Chenguang
A baseline-free damage identification method is proposed to identify damages in metallic sandwich panels with truss core in the article. The method is based on flexibility matrix and gapped smoothing method, with damage index defined DIm . The weight coefficient m is introduced to consider the effect of damages on both low-order modes and high-order modes. Numerical simulations and experiments are conducted to evaluate the present method. Besides, damage indexDI m * is also defined by processing DIm with Teager energy operator, and comparisons between DIm andDI m * are also carried out. Results show that the proposed method is effective in detecting single damage and multiple damages of the same or different extent. The weight coefficient m plays a very important role in identification of multiple damages of different styles. When comparing withDI m *, it is found that the present index DIm is better at suppressing the singularity caused by contact nodes and detecting of multiple damages which contain small or slight damages.